The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1097/mpg.0000000000001416
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Functional Abdominal Pain With Antidepressants

Abstract: Patients had significantly greater response to SSRIs than TCAs, remaining significant after controlling for psychiatric factors. Little significance is given to patient's associated gastrointestinal symptoms, frequently resulting in adverse effects and termination of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…IBS treatment is the same across different age groups, yet medication side effects and polypharmacy can lead to cautious use in older adults. Patients treated with selective serotonin reuptake inhibitors had significantly higher response and improvement in their IBS symptoms when compared to the group treated with tricyclic antidepressants (TCA) [159]. TCA and antispasmodic medications can exacerbate urinary retention, closed angle glaucoma, and cognitive impairment in elderly secondary to their anticholinergic properties.…”
Section: Large Intestinementioning
confidence: 99%
“…IBS treatment is the same across different age groups, yet medication side effects and polypharmacy can lead to cautious use in older adults. Patients treated with selective serotonin reuptake inhibitors had significantly higher response and improvement in their IBS symptoms when compared to the group treated with tricyclic antidepressants (TCA) [159]. TCA and antispasmodic medications can exacerbate urinary retention, closed angle glaucoma, and cognitive impairment in elderly secondary to their anticholinergic properties.…”
Section: Large Intestinementioning
confidence: 99%
“…A recent retrospective, single-tertiary-care-center study that investigated treatment efficacy of antidepressant use in pediatric FAP found a significantly greater response to SSRIs than TCAs even after controlling for psychiatric factors (univariate analysis P =0.03). 32 Eighty-five patients were on SSRIs (mostly citalopram). Most patients were started on low doses of 5–10 mg, which were titrated up to 60–200 mg depending on the specific SSRI.…”
Section: Ssrismentioning
confidence: 99%
“…Apart from conventional analgesics, some studies have emphasized the antinociceptive effects of antidepressants, such as imipramine. In addition, antidepressants are clinically used to control and treat different types of pain, especially neuropathic pain (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%